Analysis of the Factors Affecting the Transfer of Rice Fields to Non-Paddy Lands in the City of Mataram - Syaum Apriliani Safitri; M. Sidik; Bambang Dipokusumo; Taslim Sjah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to analyze the factors that influence the conversion of paddy fields to non-rice fields on rice production in Mataram City. In particular, the purpose of this study is to look at the factors that influence the conversion of paddy fields to non-rice fields. This study looks at the effect of annual household growth, GRDP, development of standard rice fields, the ratio of rice and non-rice fields prices, the ratio of agricultural and non-agricultural production values. To see what affects rice production in particular, namely land conversion, area of harvested land, the ratio of rice and non-rice fields prices and the ratio of agricultural and non-agricultural production values. This study uses secondary data obtained from the BPS (Central Bureau of Statistics) Mataram City office. The data is then analyzed using the multiple linear regression analysis method. The results showed that there were only 3 factors that were influential or significant, namely 1) the number of households with a coefficient value of 100.301 with a sig value of 0.022 percent, 2) GRDP coefficient value of 7.396E-8 with a sig value of 0.006 percent, 3) Standard rice field area with a coefficient value of - 1.527 with a sig value of 0.030 percent, although of the three factors there is one factor that has a negative or inversely effect. As for the factors that affect the conversion of paddy fields to non-rice fields on rice production, there is only one factor that has a real or significant effect on rice production, namely the area of rice harvested land (HA) by obtaining a coefficient value of 7.958 (sig 0.038 percent) which This means that the area of rice harvested land (HA) greatly affects the yield of rice production in the city of Mataram.